Fiqh Al-Hadist Ibn Taimiyah tentang Pluralisme Agama - Agusni Yahya (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
This paper includes nine hadiths regarding to religious pluralism or multiculturalism. Ibn Taymiyyah gave comments on each hadiths. He said, Muslims should make the instructions of the Prophet as a pattern of thinking and attitude in looking at and interacting with the Jews, Christians, Persian nation and Romanic peoples, so that Moslem people are not imitating and taking for the granted the negative behavior of non-Moslem. Fiqh al-Hadith of Ibn Taymiyyah religious pluralism that are categorized as textual is influenced by the conditions of Muslims in his time, that was most of that people did not feel proud of their views of Islam and their culture, but was attracted to the culture of other religions